Prevención de lesiones de columna vertebral mediante higiene postural en la edad escolar - Masache Patiño, Bryan Adrian (2024)
Postural hygiene is a set of postural habits and attitudes that maintain body alignment and protect and minimize the appearance of injuries and deformities, such as scoliosis, hyperkyphosis, and hyperlordosis. At school age, the spine is the most frequent place for the appearance of these injuries, approximately 41% in Latin America. The research aims to identify the effects and scope of the application of postural hygiene in the prevention of spinal cord injuries at school age through a compilation and bibliographic analysis of scientific articles. The methodological process was a bibliographic documentary type, inductive method with a qualitative and descriptive approach. After the study selection process, 35 articles were included for analysis, so we can say that poor posture in schoolchildren causes spinal injuries, and postural hygiene is vital to preventing and improving these alterations. Prevention and awareness programs have reduced malicious postures and pain and improved the overall health of children and adolescents. Implementing these school programs has had positive results; in advanced cases, physical therapy with specific exercises such as Schroth, core stabilization, Pilates, and E-Fit are effective. It is essential to promote good posture from an early age to prevent future problems and improve young people's physical and emotional well-being.